A study on outdoor accessibility in recreational areas for persons with disabilities - Ardi Herman bin Mohd Mardzi (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2010)
This study puts high concern on the persons with disabilities' (PwDs) access towards outdoor environment, their movements in parks, public spaces, utilization of outdoor facilities and the surrounding environment. The study will provide understanding upon the needs of the persons with disabilities in order to access the outdoor public areas with minimal barriers. There are a number of issues regarding lack of facilities in providing a user-friendly environment for the PwDs. These issues have been raised by various societies of the disabled persons especially from the group of hearing impaired persons, visual impaired persons, and the wheelchair users, as they need to access to spaces such as recreational areas, without any obstructions. Landscape elements, hardscape, street furniture, public facilities, gardens, open spaces and courtyards are made for the people to utilize, which also include the disabled person. However, it seems like the accessibility for this category of people is less considered by the authority, environmental designers, architects and other related parties in providing and designing a new space, building and environment. This research aims to investigate the character of outdoor public spaces that contribute to the accessibility and safety of the PwDs in recreational areas. With the case studies of Kuching Waterfront, in Sarawak and Taman Rekreasi Kiara in Kuala Lumpur, the methods applied include studies on previous researches on disabled person's accessibility, access audit exercise in two case study areas, observation and in depth interview with the disabled persons, as well as the caretakers of the disabled persons. It is hoped that information gained will indicate the level of accessibility in recreational areas in Malaysia, in general. It is also hoped that the research conducted can somehow benefit everybody from all walks of life as well as generating more ideas for the purpose of improving the recreational activities and accessibility for the PwDs.